Solid-liquid phase equilibrium and thermodynamic properties analysis of 2, 4, 5-trimethoxybenzaldehyde in mono-solvents. (December 2021) - Yu, Shuai; Cheng, Yan; Feng, Weichun; Xing, Wenguo; Li, Hongcheng; Xue, Fumin
Graphical abstract: Highlights: Solubility data of 2, 4, 5-trimethoxybenzaldehyde in nineteen mono-solvents were determined. Different thermodynamic models were used to correlate solubility data. Solubility increases with the increasing of temperature. Dissolution properties of 2, 4, 5-trimethoxybenzaldehyde were calculated based on the Wilson model. Abstract: Solid-liquid equilibrium solubility of 2, 4, 5-trimethoxybenzaldehyde (ANH) in nineteen kinds of mono-solvents (i.e., methanol, ethanol, n -propanol, i -propanol, n -butanol, i -butanol, s -butanol, n -pentanol, i -pentanol, acetone, 2-butanone, cyclohexanone, acetonitrile, N, N -dimethylformamide, tetrahydrofuran, ethyl formate, methyl acetate, ethyl acetate, and toluene) was determined by a gravimetric method over a temperature ranging from 278.15 K to 323.15 K under approximately 0.1 MPa. The solubility was positively correlated with temperature in all the selected solvents. The maximum solubility value occurred in DMF ( x 1  = 0.1923 mol·mol −1, T  = 323.15 K) and the minimum solubility value occurred in i -propanol ( x 1  = 0.001971 mol·mol −1, T  = 278.15 K). The modified Apelblat model, Yaws model, NRTL model and Wilson model were used to correlate the experimental data. The NRTL model fits best among all the models with RAD no larger than 0.0047 (ethanol) and a RMSD value less than 0.000236 (DMF). Dissolution properties of ANH, including dissolution enthalpy Δdis H, dissolution entropy Δdis S and dissolution Gibbs energy Δdis G, were calculated according to the Wilson model. The dissolution process of ANH is demonstrated to be endothermic, spontaneous, and entropy-driven in the chosen mono-solvents. The solubility data, thermodynamic parameters and dissolution properties are of guiding significance to the further investigation of ANH.